Hei whenua papatipu : kaitiakitanga and the politics of enhancing the mauri of wetlands : a thesis presented for the degree of Doctor of Philosophy, Maori Studies, Massey University, Palmerston North, New Zealand - Forster, M. E. (Massey University, 2012)
The intent of this doctoral study is to develop a better understanding of the dynamics and complexities of the contemporary practice of kaitiakitanga. There are two specific foci: Māori relationships with whenua, and; Māori-state resource management relations. Together these foci provide a platform to identify implications for the future development and practice of kaitiakitanga. Two interrelated research questions were developed to explore the contemporary practice of kaitiakitanga: what factors shape kaitiakitanga of wetland ecosystems, and; what are the affects of legislating for culture on the practice of kaitiakitanga? A case study of kaitiakitanga of Whakaki Lake, qualitative interviews with active kaitiaki and an evaluation of state environmental policies and laws were used to address these questions and theorise the dynamics and complexities of contemporary kaitiakitanga. This study begins by arguing that customary relationships between hapū and whenua and the ability of hapū to practice kaitiakitanga have been significantly influenced by the introduction of European notions of land tenure and land use. Although the ancestral landscape has changed considerably since annexation of Aotearoa New Zealand, landscapes generally and waterways specifically remain highly valued and continue to contribute significantly to the spiritual well-being and cultural identity of hapū. Transformation of the ancestral landscape, loss of native biodiversity and environmental degradation, however, continue to threaten customary relationships with whenua and the integrity of indigenous ecosystems. As a consequence, protecting the mauri of natural ecosystems has become a key priority for contemporary kaitiakitanga. Protecting the mauri of natural ecosystems is an extension of social responsibilities that emerge from a customary understanding of the environment based on mauri and whakapapa. Therefore it is argued in this study that mauri tū: restoring the balance of fragmented and degraded ancestral landscapes is an imperative that has emerged from a whakapapa-based understanding of the environment and associated relationships with whenua. In situ real life experiences of active kaitiaki involved in this study confirmed the importance of mauri tū as a tribal imperative and provide exemplars of acts of kaitiaki that enhanced or restored wetlands, lakes, waterways and associated natural resources. This study demonstrates that hapū possess a strong sustainability culture or toitūtanga, to ensure that the ancestral landscape continues to nurture the hapū and remains as a cultural and spiritual base for future generations. Tikanga tiaki or guardianship customs that facilitated environmental protection were used by the participants in this study to realise hapū obligations and responsibilities to wetland ecosystems. This demonstrated that contemporary kaitiakitanga is fluid, adaptive and has evolved into highly organised and strategic activities. New derivations of kaitiakitanga such as ecological enhancement and restoration were able to contribute to improved environmental outcomes for fragmented and highly modified wetland and waterway ecosystems. Exercising kaitiakitanga has become synonymous with participation in the state resource management system. Participation however, has only led to a limited range of opportunities for addressing Māori environmental interests. Therefore, this study argues that engagement with the state currently only provides for a limited expression of tino rangatiratanga and kaitiakitanga. The incorporation of the customary concept of kaitiakitanga into statute has resulted in the co-option of kaitiakitanga as state definitions and provisions for Māori relationships with whenua are inadequate for fully realising Māori environmental interests. Furthermore, the state controls the types of activities that can emerge, and by extension regulates Māori participation in resource management which includes the customary practice of kaitiakitanga. Therefore, by participating in the state resource management system, Māori energies are diverted away from hapū environmental priorities, obligations and responsibilities. Critical issues of ownership and addressing environmental degradation are subsumed by the state agenda. The hapū-based restoration experiences explored in this doctorate indicate that it is possible to contest the limitations that exist within current local authority practice and transform the resource management system to provide for a fuller expression of kaitiakitanga. Engagement with the state, constant political pressure and critical reflection of the integrity of the practice of kaitiakitanga are vital if Māori are to transform existing practice. Change is essential if Māori environmental interests are to receive greater attention and to ensure that local authorities are more responsive to hapū understandings of what it means to be an active kaitiaki. Māori-state contests, therefore, are critical to transform state systems, processes and practices towards greater recognition and provisions for core Māori environmental interests and kaitiakitanga.
Keywords: Wetlands restoration; Kaitiakitanga; Maori and the environment; Water resource management; Environmental policy; Whakaki Lake